A grande dor das coisas que passaram: a recordação contemplativa na crônica de Rubem Braga. - Lopes, Cícero Nicacio do Nascimento (2012)
The chronicle stands as a singular genre, especially for transiting between the fields of literature and journalism. Rubem Braga is considered one of the most representative chronicle writers in Brazilian literature, with a particular condition of being a writer who gained notoriety for only writing literary chronicles. With an extensive chronicle production started in the thirties of the last century, including about fifteen thousand chronicles, over six decades of literary journalism, the capixaba writer has left a respectable legacy of books containing collections of texts that caught popular taste. With an unusual style for the canons of his time, the chronicler Rubem Braga has composed chronicles with a cutting subjective lyricism that has enchanted generations over the years. Among his collections of chronicles, the book A borboleta amarela, object of critical and public recognition, presents texts in which the theme recurrence of the narrative of time category is noticeable, particularly the modulations of the poetic moment and duration. In these texts, we see a nostalgic narrator, restoring ambiance, past people and events, which gives clear primacy to the old days, taking a poignant and painful look raised from the perception of the transience of things and of the world and from the inexorability of the action of time.